Accounts of Thriving in the Face of Discrimination for Latina/o Undergraduate Students. Issue 1 (1st January 2023) - Morgan-Consoli, Melissa L.; Torres, Lucas; Unzueta, Emily; Meza, Daniel; Sanchez, Adriana; Vázquez, María D.; Hufana, Alyssa
ABSTRACT: Latina/o undergraduate students face many challenges, including campus climate and ethnic discrimination, which are tied to mental health problems and lower academic achievement. While always difficult, many students have reported a growth in awareness and determination afterward. Thriving or being "better off" after an adversity focuses on such perceived gains. This study explores the experiences of Latina/o undergraduate with discrimination and thriving. Semi-structured interview themes of Growth Related to Thriving were identified using Thematic Analysis.